Pemikiran Islam tentang Hubungan Negara dengan Agama: Islamic Thought on the Correlation between State and Religion - Hamzah, Hamzah; Katu, Samiang (FAI UIM, 2024)
This study discusses Islamic thought about the relationship between state and religion with sub-problems 1) a comprehensive understanding of the state and religion in the conception of Islam; 2) the views of the scholars regarding the correlation of religion and state; and 3) thoughts on reconciliation of Islamic and democracy. This research method is a literature review with a philosophical approach. The data collection method uses documentation and data analysis techniques using content analysis. The results of the study found that the state in the Islamic perspective is called al-bilad and its territory is called al-dawlah. The most important element in a country is religion itself which in Islamic perspective is called al-din and or al-millah. The scholars have different views on matters of state and religious relations. But from that difference, it can be formulated that the relationship between the state and religion is seen in the aspects of governance and democracy. Religion, in this case Islam, requires the formation of a state and gives concessions in terms of the form and technical arrangement of socio-political issues, the shape and composition of the state is not mandatory, which is important how to practice the values of the teachings of religion itself in a country. Thinking about the relationship between Islam and democracy, lies in the existence of Islamic principles about justice (al-‘adalah), freedom and equality (al-musawa), as well as upholding deliberation (al-syurah).